The Concept of Public Health from Hadith Perspective - Ikmal Ahmad Fauzi; Ecep Ismail (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to explain the concept of hadith about public health. This research is a qualitative type that applies literature study to interpret the hadith (hadith text) by using the sharah hadith approach method. The results and discussion of this study include a general view of health, an explanation of public health hadiths, and the concept of hadith about public health. This research concludes that there are many things taught by the Prophet about health through his hadiths. The hadiths listed provide an overview of how the behavior and efforts to cure disease sufferers, especially the community.